Three-dimensional single-hydrophone tracking of a sperm whale demonstrated using workshop data from the bahamas - Tiemann, Christopher O. (Canadian Acoustics, 2008)
A passive acoustic localization method for tracking the movement of a clicking sperm whale in three-dimensions using data from just one hydrophone is demonstrated using data made available for the 3rd International Workshop on Detection and Classification of Marine Mammals. One recording contains sperm whale clicks recorded on a bottom-mounted hydrophone on a steep slope of the Navy's AUTEC test range. When the direct-path acoustic ray arrivals from several clicks are time-aligned, persistent associated multipath arrivals of reflected ray paths can be identified for each click event and used for localization. Although the use of multipath arrival information is a standard procedure for range-depth tracking, a three-dimensional estimate of whale position can be obtained from the same multipath information with knowledge of an azimuthally-dependent environment relative to the receiver. In this case, azimuthal distinction arises from varied bathymetry. Multipath arrival patterns are matched to unique range-, depth-, and azimuth-dependent modeled arrival patterns to make an estimate of whale location. A threedimensional whale track in range, depth, and bearing from the fixed hydrophone is presented.